Molecular characterisation of Exon 2 of TLR2 gene and its association with Somatic cell count in Jersey crossbred cattle - Mundhe, U T; Das, D N; Gandhi, R S; Divya, P (Indian Journal of Dairy Science, 2016)
In the present study, molecular characterization of exon 2 of TLR2 gene and its association with somatic cell count in 116 Jersey crossbred cattle were carried out using PCR-RFLP. Polymorphism was observed through HaeIII, HhaI and EcoRV restriction enzymes in Created Restriction Site (CRS) exon 2-1, CRS exon 2-5 and exon 2-1 by PCR- RFLP, respectively. In CRS exon 2-1 allelic frequencies were observed as 0.857 for A and 0.142 for B alleles and relevant genotypic frequencies were 0.71 and 0.28 for genotypes AA and AB. In CRS exon 2-5, allelic frequencies were observed as 0.103 for A and 0.896 for C allele, respectively. Â The genotypic frequencies observed were 0.20 and 0.79 for genotypes AC and CC respectively. TLR2 exon 2-1 exhibited two alleles G and T with frequencies of 0.275 and 0.724, respectively with their corresponding genotypic frequencies as 0.01, 0.51 and 0.46 for GG, GT and TT genotypes respectively. Higher somatic cell counts (SCC) in GG and TT homozygous and lower in TG heterozygous genotypes were observed in exon 2-1.